MS-1 - Sofia M. Pereira PhD; Steve R. Williams PhD; Patricia Murray PhD; Arthur Taylor PhD (Molecular Imaging)
Bacterial genes involved in the biomineralization of magnetic nanoparticles in magnetotactic bacteria have recently been proposed as reporters for magnetic resonance imaging (MRI). In such systems, the expression of the bacterial genes in mammalian cells purportedly leads to greater concentrations of intracellular iron or the biomineralization of iron oxides, thus leading to an enhancement in relaxation rate that is detectable via MRI. Here, we show that the constitutive expression of the magA gene from Magnetospirillum magnetotacticum is tolerated by human embryonic kidney (HEK) cells but induces a strong toxic effect in murine mesenchymal/stromal cells and kidney-derived stem cells, severely restricting its effective use as a reporter gene for stem cells. Although it has been suggested that magA is involved in iron transport, when expressed in HEK cells, it does not affect the transcription of endogenous genes related to iron homeostasis. Furthermore, the magA -induced enhancement in iron uptake in HEK cells is insignificant, suggesting this gene is a poor reporter even for cell types that can tolerate its expression. We suggest that the use of magA for stem cells should be approached with caution, and its efficacy as a reporter gene requires a careful assessment on a cell-by-cell basis.